The Genomes of Rosaceous Berries and Their Wild Relatives (Compendium of Plant Genomes,, 2018)
This book collates the most up to date information on Fragaria, and Rubus genomes. It focuses on the latest advances in the model system Fragaria vesca, along with the allied advances in economically important crops. Covering both basic and applied aspects of crop genomics, it illustrates strategies and resources for the study and utilization of genome sequences and aligned functional genomics resources. Rosaceous berries are collectively an increasingly important set of high-value global crops, with a trade value of over £2 billion dollars per annum. The rosaceous berries strawberry, raspberry and blackberry share some common features at the genome scale, namely a range of ploidy levels in each genus and high levels of heterozygosity (and associated inbreeding depression) due to self-incompatibility systems, dioecy, or multispecies hybridization events. Taken together, although the genomes are relatively compact, these biological features lead to significant challenges in the assembly and analysis of berry genomes, which until very recently have hampered the progress of genome-level studies. The genome of the woodland strawberry, Fragaria vesca, a self-compatible species with a homozygous genome was first sequenced in 2011 and has served as a foundation for most genomics work in Fragaria and to some extent Rubus. Since that time, building upon this resource, there have been significant advances in the development of genome sequences for related crop species. This, coupled with the revolution in affordable sequencing technology, has led to a suite of genomics studies on Fragaria and more recently Rubus, which undoubtedly aid crop breeding and production in future years.